The Role of Local Wisdom on the Tradition of the Prohibition of KEBO BALIK KANDANG Marriage as an Effort of Family Resilience in Bendo Village, Ponggok Sub-District, Blitar (Javanese Spiritually Perspective, Customary Law) - Harianto, Totok; Arifin, Mochammad; Khairun Nisa, Zulia; Laili, Afrohatul (Journal of Transcendental Law, 2023)
Kebo Balik Kandang marriage is said to be a mythical procession in the community where the bride is prohibited from marrying a man who lives in the same region as her biological father. This means that even though the bride comes from a village outside the region, if there is a track record of the bride’s village-born origin categorized as a Kebo Balik Kandang marriage type design, mythically it has a significant influence on the pattern of her family’s resilience. Family resilience means managing physical and non-physical resources and facing problems with the aim of achieving a quality family as a foundation in maintaining national resilience. Research in Bendo Village aims to examine the community’s views on kebo balik kandang marriages and how they maintain household resilience. The results show that the perpetrators of kebo balik kandang marriages face many challenges in their marriage journey. However, there is one family who managed to live a good marriage through mutual submission, love, care, good communication, and pleasant interaction. According to Islamic studies, their marriage is in accordance with sharia and there are no prohibited blood ties.